PERAN NON-GOVERNMENT ORGANIZATION (NGO) DALAM MENDORONG PENANGANAN ISU LINGKUNGAN HIDUP DI INDONESIA - Umi Umairah Suhardi; Riskayanti; Mar'atun Fitriah; Nurul Shalihat Ansar (Jurnal Hukum Unsulbar, 2024)
This research examines the role of Non-Government Organizations (NGOs), especially GreenpeaceID, in advocating environmental issues in Indonesia. The research uses qualitative methods with secondary data analysis sourced from official Greenpeace reports, scientific articles and mass media news. Greenpeace plays a strategic role through three main approaches: legal advocacy, advocacy regarding business permits, and public campaigns via social media. Through these activities, Greenpeace not only monitors environmental violations, but also encourages policy reform and increases public awareness of the importance of environmental sustainability. This research provides in-depth insight into the contribution of NGOs in dealing with environmental problems in Indonesia. Keywords : NGOs, GreenpeaceID, Environmental Issues, and Social Movements